Three genes and two isozymes: Gene conversion and the compartmentalization and expression of the phosphoglycerate kinases of Trypanosoma (Nannomonas) congolense - Parker, H.L.; Hill, T.; Alexander, K.; Murphy, N.B.; Fish, W.R.; Parsons, M. (Elsevier, 1995)
The glycosome, a microbody organelle found only in kinetoplastid protozoa, compartmentalizes the first six enzymes of glycolysis. In order to better understand the regulation and targeting of glycolytic enzymes in trypanosomes. We have cloned and analyzed the three genes within the complex is similar to that of Trypanosoma brucei brucei. The nucleotide and amino-acid sequences, including those of the novel high-molecular-weight 56PGK, show substantial cross-species similarity. However, the two downstream genes, clPGK and c2PGK, encode identical isozymes in T. congolense, while they encode distinct glycosomal and cytoplasmic isozymes in T. brucei. Western analysis also indicated that there are only two isozymes in T. congolense and that these are constitutively expressed. Differential digitonin solubilization of the trypanosomes indicated that 56PGK is primarily localized to the glycosome, as expected, and that cl/c2PGK is cytoplasmic, Northern analysis demonstrates that while 56PGK is constitutively expressed, clPGK and c2PGK mRNAs are differentially expressed in the T. congolense developmental stages. This work demonstrates that T. congolense has only one PGK isozyme, 56PGK, that is predominantly localized in glycosomes.